Surface and interface properties of carbon fiber composites under cyclical aging - Lv, Xinying; Wang, Rongguo; Liu, Wenbo; Jiang, Long (Applied surface science, 2011)
[Display omitted] ► Subject carbon fiber–reinforced BMI composites to combination cycling aging. ► Determine the flexural and inter-laminar shear strength of composite at various aging intervals. ► Characterize the composite at various aging intervals accordingly. ► Analyze the effects of cycling aging on surface and interface properties of carbon fiber–BMI composites. Carbon fiber–reinforced BMI composites have been subjected to combination accelerated aging comprising a hygrothermal process, a thermal-oxidative process, and a freezing process in order to simulate their responses under complicated service environments. This cyclical condition, including the freezing process, has not been investigated by other researchers so far. The effects of this combination accelerated aging on the mechanical properties have been characterized by FTIR, SEM/EDXA, XRD, and moisture-uptake determination. The results indicated that combination accelerated aging had great effects on the mechanical properties of the composite, the network structure of the BMI matrix, and the moisture uptake by the composite. After a third cycle of accelerated aging, moisture reached the center layer of the composite and as a result led to an obvious decrease in ILSS due to deterioration of the carbon fiber–BMI interface. Sufficient moisture absorption on the composite surface made the network structure of the BMI matrix more open, which facilitated stress relaxation and the creation of micro-cracks, with a consequent obvious decrease in flexural strength. With increasing number of combined-action accelerated aging cycles, ever more moisture was absorbed during each hygrothermal process due to the plasticizing effect of water, and micro-cracks propagated as a result of internal stresses caused by the hygrothermal process, the thermal-oxidative process, and the freezing process of each cycle. XRD analysis indicated that moisture penetrated through the amorphous region of the BMI matrix.